Potential of Fruit Peel Extracts in Dissolving Simulated Renal Stones in In vitro Conditions - Varicola, Karuna Sree; Amreen Siddiqua A.; Dintyala, Keerthi; Ventrapati, Gandhi (Pharmaceutical Research - Recent Advances and Trends Vol. 3, 2024)
Objective: The present study evaluates the antiurolithiatic activity of selected fruit peels on simulated renal stones in in vitro conditions. Background: Fruit peels are discarded in the majority of common fruits even though they are found to be safe for consumption. Fruit peels are rich in antioxidants and are the best source of rough dietary fiber. Apple peel possesses a high content of phenolic compounds which imparts anti-proliferative activity [1] and antioxidant activity. Methods: Simulated renal stones were prepared by homogenous precipitation method. The criterion selected was to estimate the amount of calcium oxalate remaining in the semi-permeable membranes by Kramer and Tisdal method with slight modification. A suitable media was provided by the TRIS buffer. Results: The crude methanol extract of Musa sapientum exhibited the highest dissolution of calcium oxalate ie.9.15 mg and the percent dissolved was found to be 91.5% in comparison to Malus pumila methanol extract which dissolved 8.96 mg (89.6%) and Punica granatum methanol extract which dissolved 8.0 mg (80.0%). Its activity was comparable with that of the standard drug Tamsulosin hydrochloride (400 mg) with a percentage dissolved of about 90.5%. The expected mechanism for the phytoconstituents present in the tested extracts in the management of urolithiasis includes diuretic, antispasmodic, and antioxidant activity, as well as an inhibitory effect on crystallization, nucleation, and aggregation of crystals. Conclusion: Experimental evidence showed that methanol and aqueous fruit peel extracts of Musa sapientum, Malus pumila, and Punica granatum possess potential antiurolithiatic activity. Their effect is found to be significant and the extracts can be used in the treatment of lithiasis. Further, in vivo studies are needed to give a strong scientific basis for these in vitro findings.